Autologous serum eye drops for ocular surface disorders- a clinical study - Sahu, Vijaya; Pandey, Nidhi; Chandrakar, A K; Garg, M.L. (International Journal of Medical Research and Review, 2015)
Introduction: Tears have antimicrobial, nourishing, mechanical and optical properties. Several tear factors that have been identified to be, of importance in the maintenance of normal corneal and conjunctiva epithelium. A lack of these factors results in severe ocular surface disorders. Autologous serum in the form of eye drops has been reported as an effective treatment for severe ocular surface disorders. The present study was designed to determine the efficacy and safety of autologous serum application in various ocular surface disorders. Methods: This is a prospective case analysis of 30 eyes of 18 patients between June 2009 & November 2010. The following tests were performed: Schirmer I, Basic secretion test, Tear film Breakup time, Fluorescein staining, Rose Bengal Staining. 20% concentration of Serum eye drop was used for 30 days and no other tear substitutes were prescribed to patients while during treatment. Results: After one month treatment marked improvement was observed - 19 eyes in Schirmer I, 18 eyes in Basic tear secretion, 23 eyes in tear film Break up time, 21 eyes in Fluorescein staining pattern and 29 eye in Rose Bengal staining pattern. Conclusion: It was observed that Hypovitaminosis A and Neurotrophic keratitis showed 100% improvement, kerato conjunctivitis sicca, sjogren’s syndrome, persistent epithelial defect, Recurrent erosion syndrome, Marginal corneal ulcer also showed excellent results but Stevens - Johnson syndrome showed very poor response to treatment.